Lipid Peroxidation in Silver Pomfret Muscle at 0 and 10°C - P.G., Viswanathan Nair (Fishery Technology, 2025)
The levels of peroxide in pomfret muscle during storage at 0 and 10°C were studied. Peroxide concentration was higher at HfCduring the early stages. After six to eight days, peroxide levels started to decrease at the higher temperature while at the lower temperature it went on increasing till the 19th day. The maximum peroxide value obtained at lO"C was much less than that obtained at 0°C.